Identification of novel chemical structures of sulfo-imidazolium zwitterionic-type salt basis on 2D NMR analysis - Khaligh, Nader Ghaffari; Ling, Ong Chiu; Johan, Mohd Rafie; Juan, Joon Ching (Elsevier, 2019)
The reaction of the equimolar mixture of imidazole and 1,4-butanesultone was performed at 90 °C in ethylbenzene for 12 h and the zwitterionic and ionic structures of the product investigated by the NMR analysis. The present work displayed the great importance of 2D NMR analysis on the structure elucidation of this sulfonic acid functionalized liquid salt. The results of NMR analysis demonstrate that 4-imidazole-1-yl-butane-1-sulfonic acid did not exist and really a mixture of zwitterionic and ionic compounds is produced.